2002
DOI: 10.1128/jvi.76.12.5857-5865.2002
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Requirement for Two Stages of Protein-Primed Initiation of Reverse Transcription in Hepadnaviruses

Abstract: Reverse transcription in hepadnaviruses is primed by the viral reverse transcriptase (RT) (protein priming) and requires the specific interaction between the RT and a viral RNA signal termed , which bears the specific template sequence for protein priming. The product of protein priming is a short oligodeoxynucleotide which represents the 5 end of the viral minus-strand DNA and is covalently attached to the RT. We have now identified truncated RT variants from the duck hepatitis B virus that were fully active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 36 publications
(44 reference statements)
3
42
1
Order By: Relevance
“…Therefore, the results obtained with both omission of dNTPs and inclusion of ddNTPs were consistent with the notion that the DNA polymerization product synthesized, under these conditions, from priming sites in the TP (mostly from the cryptic site or sites, see Fig. 7 below) and RT (exclusively from the cryptic site or sites) domains had the sequence d(GTA(A)), the same as the polymerization product previously shown for the authentic Y96 site (50,54), and thus was likely templated by the same ε internal bulge sequence (UUAC).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Therefore, the results obtained with both omission of dNTPs and inclusion of ddNTPs were consistent with the notion that the DNA polymerization product synthesized, under these conditions, from priming sites in the TP (mostly from the cryptic site or sites, see Fig. 7 below) and RT (exclusively from the cryptic site or sites) domains had the sequence d(GTA(A)), the same as the polymerization product previously shown for the authentic Y96 site (50,54), and thus was likely templated by the same ε internal bulge sequence (UUAC).…”
Section: Resultssupporting
confidence: 74%
“…Since the cryptic sites in the TP and RT domains were able to initiate DNA synthesis, we were interested in determining whether these sites could also support subsequent DNA polymerization. We have recently shown that MiniRT2 was able to carry out DNA polymerization, i.e., the extension of the single dGMP attached to the protein to form a short (several nucleotides long) DNA oligomer in the presence of Mn 2ϩ but not in the presence of Mg 2ϩ (27,54). Therefore, we performed transcomplementation in Cryptic site priming shared the same nucleotide preference as the authentic site priming.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, by removing the N-terminal third of TP, most of the spacer, part of the RT domain (the putative thumb subdomain), and the entire RNase H domain, we have recently isolated a truncated RT protein from the duck HBV (DHBV), MiniRT2, which no longer strictly depends on the host chaperones for protein priming (55). Strikingly, MiniRT2 is able to initiate protein priming by covalently attaching the first nucleotide (dGMP) to the primer tyrosine residue in TP but is unable to carry out any additional DNA synthesis to complete protein priming (54). This result suggests that protein priming can be further divided into two distinct steps: the covalent attachment of the first nucleotide to RT (initiation) and the subsequent addition of 2 or 3 nt to the initiating nucleotide (polymerization).…”
mentioning
confidence: 99%